1991
DOI: 10.1080/00021369.1991.10870930
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Properties of a Hydrogen Sulfide-binding Protein That Is Involved in Sulfur Oxidation ofThiobacillus ferrooxidans

Abstract: A hydrogen sulfide: ferric ion oxidoreductase (SFORase), which is crucial in sulfur oxidation of T. ferrooxidans AP19-3, oxidizes hydrogen sulfide with Fe 3 + as an electron acceptor to give sulfite ion and Fe 2 +. When washed intact cells of T. ferrooxidans AP19-3 were treated with hydrogen sulfide solution (100 mM) at pH 6.5 for 1 hr, a heat stable reduced sulfur containing protein, which serves as a reduced sulfur compound for purified SFORase to give sulfite, was formed in the plasma membrane of this strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The amount of H 2 was quantified by gas chromatography (GC-14A; Shimadzu, Kyoto, Japan) with a thermal conductivity detector. The amount of H 2 S was quantified by the methylene blue method as described elsewhere (45). The amounts of gas metabolites generated were normalized by cell mass, which was determined by measuring the turbidity of the culture broth.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of H 2 was quantified by gas chromatography (GC-14A; Shimadzu, Kyoto, Japan) with a thermal conductivity detector. The amount of H 2 S was quantified by the methylene blue method as described elsewhere (45). The amounts of gas metabolites generated were normalized by cell mass, which was determined by measuring the turbidity of the culture broth.…”
Section: Methodsmentioning
confidence: 99%
“…43) A hydrogen sulfide-binding protein, which reversibly bound hydrogen sulfide, has been purified from the membrane fraction of A. ferrooxidans AP19-3. 44) Banco and Ingledew also found that A. ferrooxidans released a small amount of hydrogen sulfide during aerobic and anaerobic incubation with elemental sulfur, suggesting that the activation step in sulfur oxidation might involve an initial reductive step of elemental sulfur. 45) Although the enzymatic mechanism for the production of hydrogen sulfide under aerobic conditions is still unclear, hydrogen sulfide does occur in A. ferrooxidans cells.…”
Section: Enzyme Activities Of Iron-and Sulfur-grown Cellsmentioning
confidence: 98%
“…Hydrogen sulfide was measured by the methylene blue method. 19) The reaction mixture contained 400 p,l of 0.1 M sodium citrate buffer (pH 6.0), 50 p,l of 10 mM NAD H, 100 p,l of 10 mM sodium thiosulfate, and enzyffii~ solution. Total volume was 600 p,l.…”
Section: Methodsmentioning
confidence: 99%
“…After incubating the reac-tion mixture at 4SoC for S min, the reaction was started by adding sodium thiosulfate and stopped by adding 200 {ll of 2 M NaOH. Deionized water (800 {ll) and diamine-ferric chloridle solution (400 {ll) 19) were added to the solution. The blue color resulting from the production of methylene blue was measured by a Shimadzu UV-1200 spectrophotometer at 670nm.…”
Section: Methodsmentioning
confidence: 99%